PENGARUH SUPERVISI PEMBELAJARAN KEPALA SEKOLAH TERHADAP KINERJA GURU YANG DIMODERASI IKLIM SEKOLAH PADA SMP MARDIWIYATA - Suprianto, Matius Eko; Imron, Ali; Juharyanto, Juharyanto (Universitas Tanjungpura, 2025)
Besides managerial responsibilities, principals are obliged to assist teachers in training and improving their teaching performance. Supervision is the teacher training efforts so that the implementation of their professional duties runs well and provides an increase in student learning achievement. This research was conducted at the Mardi Wiyata school in East Java. Research used quantitative descriptive methods, with a sample size 91 teachers, calculations using PLS SEM, outer model testing (validity and reliability) and inner model testing. Results is a direct influence of supervision on teacher performance 42.3%; supervision of school climate 47.8%; The influence of school climate on teacher performance 49.5%, and the indirect influence of supervision on performance which is moderated by school climate 23.7%. Conclusion the supervision contributes to improving teacher performance which is influenced by school climate to support the teaching and learning process.